The Biological Properties of the Essential Oil from the Jordan Accession of Phagnalon sinaicum Bornm. & Kneuck. - Natale Badalamenti; Michela Di Napoli; Giusy Castagliuolo; Mario Varcamonti; Maurizio Bruno; Anna Zanfardino (Plants, 2023)
The genus Phagnalon Cass. (Asteraceae) is composed of widely distributed species and most of them, due to the medicinal properties they possess, are widely used in folk medicine but also as spices in the culinary field. The polar and non-polar extracts, as well as the complex mixtures of their essential oils, from several Phagnalon species and ssp., have shown antibiotic, antiviral, cytotoxic, and several other biological properties. In this work, the chemical composition and the antimicrobial, cytotoxic, and antioxidant properties of the Jordan accession of Phagnalon sinaicum Bornm. & Kneuck. essential oil (EO), an extremely rare plant that grows in ravines in the Middle East, were investigated. The EO, analyzed by GC-MS, was found to be rich in terpenoid compounds, and, in particular, in oxygenated monoterpenes, with the main compound being artemisia ketone (22.3%), followed by α-thujone (17.7%), and santolin alcohol (14.8%). The EO had good antimicrobial activity, especially against Escherichia coli Gram-negative bacterium (3 mg/mL MIC values) and was also effective in counteracting in vitro biofilm formation. Furthermore, this EO showed low cytotoxicity against immortalized human keratinocytes lines, but had good antioxidant activity on the same eukaryotic cellular models.